Valoración socioambiental de los recursos naturales existentes en el bosque humedo de la cordillera occidental de Los Andes, en la provincia de Cotopaxi, parroquia Pilaló y Tingo La Esperanza en el periodo 2021 – 2022. - Ponce Galárraga, Indira Poleth (2022)
The socio-environmental assessment of the existing natural resources in the humid forest of the Western Cordillera of the Andes was carried out in this research; its objectives were: to analyze the socio-environmental behavior of the forest, determine the natural resources and assess the current behavior of the natural landscape of the humid forest, the exploratory research was established to make an approximation to the data obtained, considering the descriptive method for the analysis and systematization of the information, in addition to applying the ArcGis software for the elaboration of the maps of the sector; it was assessed the current state of the humid forest, considering 63 people from the place of incidence, who mentioned that they see the exploitation of natural resources as a source of income, this allowed to accurately identify and quantify each of the aspects studied in the different stages, while the Bureau of Land Management (BLM) method established as a result that the forest is currently in a process of advanced deterioration due to the different activities of anthropogenic origin currently developed, as well as the introduction of animal and plant species that have modified its structure altering the ecosystem balance of the place, according to the Shannon index, a result of 2.59 was obtained, which allows establishing that the forest currently has a normal state, while the Simpson diversity index presented a result of 12.71, which reflects that there are a more significant number of species. Concerning the BLM method, it is determined that the landscape units are established as areas of high and medium sensitivity, with a predominance of MEDIUM sensitivity, due to the development of different activities of anthropogenic origin, and it is essential to take protection measures for the conservation of this vitally important area.